In vitro initial stability of a stemless humeral implant. (February 2016) - Favre, Philippe; Seebeck, Jörn; Thistlethwaite, Paul A.E.; Obrist, Marc; Steffens, Jason G.; Hopkins, Andrew R.; Hulme, Paul A.
Abstract: Background: Stemless humeral prostheses have been recently introduced. We measured for the first time their in vitro primary stability and analyzed the influence of three clinically important parameters (bone quality, implant size and post-operative loading) on micromotion. We also assessed if displacement sensors are appropriate to measure implant micromotion. Methods: A stemless humeral implant (Sidus® Stem-Free Shoulder, Zimmer GmbH, Winterthur, Switzerland) was implanted in 18 cadaveric humeri. Three-dimensional motion of the implant was measured under dynamic loading at three load magnitudes with displacement sensors. Additionally, the relative motion at the bone–implant interface was measured with an optical system in four specimens. Results: Micromotion values derived from the displacement sensors were significantly higher than those measured by the optical system ( P  < 0.005). Analysis of variance (ANOVA) indicated that bone density ( P  < 0.0005) and load ( P  < 0.0001) had a significant effect on implant micromotion, however the effect of implant size was not statistically significant ( P  = 0.123). Interpretation: Micromotion of this stemless design was shown to be significantly dependent on cancellous bone density. Patients must therefore have adequate bone quality for this procedure. The influence of load magnitude on micromotion emphasizes the need for controlled post-operative rehabilitation. Measurements with displacement sensors overestimate true interface micromotion by up to 50% and correction by an optical system is strongly recommended. Highlights: Primary stability of a novel stemless humeral implant was assessed using two methods. Bone quality has a significant influence on micromotion. Joint load has a significant influence on micromotion. Implant size has no influence on micromotion. Displacement sensors overestimate true micromotion, optical system are recommended.